Penerapan Altman Z-Score Dalam Memprediksi Kebangkrutan Pada PT Bank Mandiri (Persero) Tbk - Eva Malina Simatupang (JURNAL AKUNTANSI BARELANG, 2020)
The purpose of this study is to determine and analyze the risk of bankruptcy of goverment PT Bank Mandiri (Persero) Tbk by Altman Z-Score. Population of this study is PT Bank Mandiri (Persero) Tbk financial statements and sample of this study is PT Bank Mandiri (Persero) Tbk financial a statements 2014– 2018. Data type used is secondary data and data collection technique is documentation from financial statements published on www.bankmandiri.co.id. Data processing technique used Altman Z-Score methode Modification version. Based on the result data processing, obtained results Z-Score at 2014 is 2,04; 2015 is 2,13; 2016 is 1,98; 2017 is 2,10 and 2018 is 2,22. Based on the data analyze it can be concluded PT Bank Mandiri (Persero) Tbk is categorized suffed the threat of Grey Area because the standart score value below 1,81 < Z < 2,99 and PT Bank Mandiri (Persero) Tbk had the highest risk of bankcruptcy in 2016 with Z-Score in 1,98.